Microencapsulated carvacrol and cinnamaldehyde replace growth-promoting antibiotics: Effect on performance and meat quality in broiler chickens - BOSETTI,GILNEI E. (2020)
Abstract The aim was to evaluate the use of mixture of microencapsulated carvacrol and cinnamaldehyde as a replacement for growth-promoting antibiotics in broiler diets on performance, intestinal quality, organ development, carcass yields and cuts, and meat quality. In the trial were used 600 male chicks, allocated in a completely randomized design, with five treatments and eight replicates of 15 birds, reared up to 41 days of age. The treatments were: Negative Control (NC), Positive Control (PC) 30 mg/kg of virginiamycin, NC+100 mg/kg of essential oils, NC+200 mg/kg of essential oils and NC+400 mg/kg of essential oils. Essential oils were composed by a micro-encapsulated blend, with of 60% cinnamaldehyde, 30% carvacrol and 10% carrier. Birds received essential oils achieved performance equivalent to those birds received PC diets, having better development than NC broilers. No differences were found on relative organ weight, intestinal mucosa and meat quality parameters, however, higher villus:cript ratio was found in PC, NC+200 and NC+400 groups. Meat crude protein and yellowness were influenced by inclusion of carvacrol and cinnamaldehyde. It was concluded microencapsulated carvacrol and cinnamaldehyde can replace growth-promoting antibiotic in broiler diets, ensuring performance, intestinal integrity and broiler meat quality.